Evaluation of plasma activated liquids for the elimination of mixed species biofilms within endoscopic working channels - Naomi Northage; Vasyl Shvalya; Martina Modic; Thorsten Juergens; Sascha Eschborn; Malcolm J. Horsburgh; James L. Walsh (Scientific Reports)
Abstract The use of reusable flexible endoscopes has increased dramatically over the past decade, however despite improvements in endoscope reprocessing, the continued emergence of endoscopy-associated outbreaks as a result of multi-drug resistant bacteria has highlighted the need for a new approach to disinfection. Here, the use of plasma activated liquids (PALs) for the elimination of mixed species biofilm contamination within the working channels of endoscopes was evaluated. Cold atmospheric pressure plasma was used to chemically activate water and a commercially available pH buffered peracetic acid to create PALs. Polytetrafluoroethylene endoscope surrogate test pieces were contaminated with clinically relevant mixed species biofilms. The efficacy of PALs for the decontamination of narrow lumens was compared against the commercial disinfectant. Plasma activation was found to increase the antibiofilm capabilities of pH buffered peracetic acid by introducing reactive chemical species into the solution. Disinfection of endoscopic test pieces with plasma activated disinfectant (PAD) resulted in a 7.30 log10 reduction of biofilm contamination in 5 min, surpassing the 4.39 log10 reduction observed with the currently used endoscope disinfection method. PAD also resulted in reduced regrowth and recolonization of the surface of the endoscopic test pieces. Minimal changes to the surface morphology and composition were observed following exposure to PAD in comparison to the commercial disinfectant, suggesting the developed approach is no more aggressive than current disinfection approaches.